Students' Perception on the Implementation of English Hybrid Classes in Islamic University and National University in Indonesia - Gigih Ariastuti Purwandari; Eka Dyah Puspita Sari; Indah Puspitasari (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2022)
Various virtual learning environments have been implemented during the emergence of the Covid-19 pandemic. Hybrid learning is a virtual learning environment in which half of the students attend the class physically while others join virtually. This model was adopted by students in two different universities in Central Java, namely Jenderal Soedirman University (Unsoed) and State Islamic University of Prof. K.H. Saifuddin Zuhri (UIN Saizu) Purwokerto. The purpose of this study is to investigate the students’ perceptions of hybrid learning in two different universities as well as to find out the challenges during the implementation of hybrid learning. There were 88 participants taken as subjects from both universities. This study was a qualitative method that used observation and questionnaires to collect data from participants. The result shows that the students have positive perceptions during hybrid learning that could affect their performance. The positive perception was hybrid classes provided flexible time, upgraded technology mastery, and built social interaction with others. Moreover, this study also found some obstacles such as technical issues and students’ surroundings or environment that have been affecting their performance.